The Effect of Organizational Culture on Employee Job Satisfaction - Jumana, Mariyam (2016)
The study attempt to examines the impact of organizational cultures on employee job satisfaction. In this study four company with four different dominant cultures are explored. The sample includes, Company A a family business signifying clan culture, Company B Information Technology Company indicating adhocracy culture, Company C hardware franchise representing market culture and Company D an automobile company signifying hierarchy culture. Data was accumulated for the research through interviews and surveys. Surveys were collected from employees at all level of the organizations and two interviews from HR manager and executive/line manager were conducted. Data was analyzed using SPSS software, descriptive analysis and correlation was used for this research. The result obtained indicates that clan culture and adhocracy culture have strong positive linear relationship with job satisfaction, market culture has moderate correlation and hierarchy culture have a weak correlation with job satisfaction. Recommendation was presented based on the finding and information from the study.